Role of DNA Damage Response in Suppressing Malignant Progression of Chronic Myeloid Leukemia and Polycythemia Vera: Impact of Different Oncogenes - Stetka, Jan; Gursky, Jan; Liñan Velasquez, Julie; Mojzikova, Renata; Vyhlidalova, Pavla; Vrablova, Lucia; Bartek, Jiri; Divoky, Vladimir (Cancers, 2020)
Inflammatory and oncogenic signaling, both known to challenge genome stability, are key drivers of BCR-ABL-positive chronic myeloid leukemia (CML) and JAK2 V617F-positive chronic myeloproliferative neoplasms (MPNs). Despite similarities in chronic inflammation and oncogene signaling, major differences in disease course exist. Although BCR-ABL has robust transformation potential, JAK2 V617F-positive polycythemia vera (PV) is characterized by a long and stable latent phase. These differences reflect increased genomic instability of BCR-ABL-positive CML, compared to genome-stable PV with rare cytogenetic abnormalities. Recent studies have implicated BCR-ABL in the development of a "mutator" phenotype fueled by high oxidative damage, deficiencies of DNA repair, and defective ATR-Chk1-dependent genome surveillance, providing a fertile ground for variants compromising the ATM-Chk2-p53 axis protecting chronic phase CML from blast crisis. Conversely, PV cells possess multiple JAK2 V617F-dependent protective mechanisms, which ameliorate replication stress, inflammation-mediated oxidative stress and stress-activated protein kinase signaling, all through up-regulation of RECQL5 helicase, reactive oxygen species buffering system, and DUSP1 actions. These attenuators of genome instability then protect myeloproliferative progenitors from DNA damage and create a barrier preventing cellular stress-associated myelofibrosis. Therefore, a better understanding of BCR-ABL and JAK2 V617F roles in the DNA damage response and disease pathophysiology can help to identify potential dependencies exploitable for therapeutic interventions.
Keywords: polycythemia vera; chronic myeloid leukemia; DNA damage response; ATM-Chk2 pathway